2011
DOI: 10.1021/cn2000519
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward Positive Allosteric Modulators of the Metabotropic Glutamate Receptor Subtype 5 (mGlu5)

Abstract: ABSTRACT:This Review describes recent trends in the development of small molecule mGlu 5 positive allosteric modulators (PAMs). A large body of pharmacological, genetic, electrophysiological, and in vivo behavioral evidence has accumulated over the past decade which continues to support the hypothesis and rationale for the activation of the metabotropic glutamate receptor subtype 5 (mGlu 5 ) as a viable and promising target for the development of novel antipsychotics. Until recently, functionally efficacious a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 84 publications
1
79
1
Order By: Relevance
“…In light of our previous findings in which an mGluR5 agonist injected into the nucleus accumbens potentiated the interoceptive effects of a low alcohol dose (0.5 g/kg) under control conditions (Besheer et al, 2009), we hypothesized that systemically administered CDPPB would potentiate the discriminative stimulus effects of alcohol under 'normal' conditions. The CDPPB dose range tested is considered to be moderate (see Stauffer, 2011) and was selected based on pilot experiments in our lab and previously published work (Clifton et al, 2013;Fowler et al, 2011;Gass and Olive, 2009;Stefani and Moghaddam, 2010). Therefore, there is strong possibility that a higher dose range may have potentiated the interoceptive effects of alcohol, and this would need to be examined before concluding that positive allosteric modulation of mGluR5 does not potentiate the interoceptive effects of alcohol under basal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In light of our previous findings in which an mGluR5 agonist injected into the nucleus accumbens potentiated the interoceptive effects of a low alcohol dose (0.5 g/kg) under control conditions (Besheer et al, 2009), we hypothesized that systemically administered CDPPB would potentiate the discriminative stimulus effects of alcohol under 'normal' conditions. The CDPPB dose range tested is considered to be moderate (see Stauffer, 2011) and was selected based on pilot experiments in our lab and previously published work (Clifton et al, 2013;Fowler et al, 2011;Gass and Olive, 2009;Stefani and Moghaddam, 2010). Therefore, there is strong possibility that a higher dose range may have potentiated the interoceptive effects of alcohol, and this would need to be examined before concluding that positive allosteric modulation of mGluR5 does not potentiate the interoceptive effects of alcohol under basal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that selective activators of the mGlu 5 subtype could provide an exciting new approach for treatment of schizophrenia and other disorders that lead to impaired cognitive function (Gregory et al, 2011;Vinson and Conn, 2012). Although discovery of selective mGlu 5 agonists that have drug-like properties has been challenging, there have been major advances in development of highly selective positive allosteric modulators (PAMs) for mGlu 5 (Liu et al, 2008;Conn et al, 2009;Stauffer, 2011;Varnes et al, 2011;Packiarajan et al, 2012). A diverse range of selective mGlu 5 PAMs have now been identified that have efficacy in animal models used to predict potential antipsychotic and cognitive enhancing activity (Gregory et al, 2011;Vinson and Conn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Selective mGlu 5 PAMs have been developed from multiple chemical scaffolds (O'Brien et al, 2004;Kinney et al, 2005;Chen et al, 2007;Liu et al, 2008;Hammond et al, 2010;Rodriguez et al, 2010;Lamb et al, 2011;Stauffer, 2011;Varnes et al, 2011;Noetzel et al, 2012;Packiarajan et al, 2012); the majority of these mGlu 5 PAMs bind to the same site as the prototypical mGlu 5 negative allosteric modulator (NAM) MPEP (2-Methyl-6-(phenylethynyl)pyridine), located in the top third of the transmembrane spanning domains, involving transmembrane domains 3, 6, and 7 (Gregory et al, 2011). However, at least two mGlu 5 PAMs, CPPHA (N-(4-chloro-2-[(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)methyl] phenyl)-2-hydroxybenzamide) (O'Brien et al, 2004;Zhao et al, 2007;Chen et al, 2008) and VU0357121 (Hammond et al, 2010), have been identified that interact noncompetitively with the MPEP site.…”
Section: Introductionmentioning
confidence: 99%
“…We searched our available mGlu 5 allosteric antagonists to identify novel compounds with weak negative cooperativity. In screening compounds within the picolinamide acetylene class series (Stauffer, 2011;Bridges et al, 2013;Turlington et al, 2013;, we noted that the mGlu 5 NAM VU0477573 (C 18 ,H 17 ,FN 2 O; molecular weight 5 296.34) showed limited negative cooperativity in inhibiting the glutamate EC 80 -induced intracellular calcium release in HEK293A cells stably expressing rat mGlu 5 (HEK293A-rat-mGlu 5 -low). The structure of VU0477573 is shown in comparison with the prototypical biaryl acetylene scaffold of the mGlu 5 NAMs MPEP and MTEP (Fig.…”
Section: Resultsmentioning
confidence: 99%